Lavender Aromatherapy to Treat the Symptoms of Restless Leg Syndrome in Patients Undergoing Hemodialization - Etik Rositasari; Arina Maliya (Universitas Muhammadiyah Semarang, 2022)
Hemodialysis is one of the renal replacement therapy for patients with chronic kidney failure which could give some complications including Restless Leg Syndrome. Non-pharmacological therapies such as lavender can be used to reduce the symptoms caused by RLS. The purpose of this study was to examine several literature, articles and research documents that identified the effectiveness of lavender aromatherapy in overcoming the symptoms caused by RLS in patients undergoing hemodialysis. The method used in this study is a literature review conducted with reference to searches through online database sites, namely Google Scholar, ScienceDirect, Pubmed and ResearchGate. The results of the study from 7 reviewed articles showed that lavender therapy given through various interventions could reduce reduction, reduce fatigue and reduce RLS scores. The conclusion obtained in this study is that the intervention with lavender aromatherapy has been shown to reduce the symptoms caused in hemodialysis patients who experience RLS so nurses need to consider lavender aromatherapy as an intervention in hemodialysis patients who experience RLS.